A Review of Methodological Approaches to Authenticating the Geographical Origin of Wines - Nonna V. Gnilomedova; Nadezhda S. Anikina; Alexander Yu. Kolesnov (Техника и технология пищевых производств)
Wines with a clear geographical origin are more attractive for customers. The geographical origin of wine is stated on its label, but no official standards guarantee its reliability. The present research objective was to analyze the existing methodological approaches to wine authentication. The study featured domestic and foreign publications indexed in Dimensions and Elibrary in 2017–2022 with such keywords as wine authentication, geographical origin of wine, and chemometrics. The research revealed no single methodological solution to wine authentication because food science knows a wide range of parameters, methods, analytical equipment, and data processing models. Chemometric methods are reliable because they are able to process large arrays of analytical research results structured in a data bank using the so-called fingerprint principle. They involve 2–65 markers that are individual for each geographical region, country, zone, or terroir. Another promising method is the quantitative and qualitative nuclear magnetic resonance spectroscopy (qNMR) of protons 1H and deuterium 2H(D) nuclei, as well as other elements (13C, 17O, 31P, 14N). The review resulted in an integrated approach based on a combination of isotopic testing with cation-anionic profiling. The analytical support involved the methods of atomic absorption and atomic emission spectroscopy, spectrometry with inductively coupled plasma, isotope ratio mass-spectrometry, and quantitative and qualitative nuclear magnetic resonance spectroscopy. This combined approach could provide background for an all-Russian state standard with a single algorithm for wine authentication tests. The new approach will be used to develop enochemical profiles of wines from a particular region, as well as to choose the most effective chemometric models for geographical authentication.